(untitled) (Research, Society and Development, 2021)
Aim: In this study was evaluated the fracture resistance of endodontically treated maxillary premolars restored with different restorative materials. Methods: Sixty maxillary premolars were submitted to the same mesio-occlusal-distal cavity preparation, endodontic treatment and divided into 5 groups (n = 10): Coltosol Group – GCO restored with calcium silicate material; Glass Ionomer Cement Group – GGIC, restored with Maxxion R; Modified Glass Ionomer Cement – GMGIC, restored with Gold Label 2; Composite Group - GC, restored with Z100, and the positive control group (GP) - left unrestored. One group remained intact (n=10) serving as negative control (GN). Samples were subjected to fracture resistance testing by the universal testing machine until fracture occurred and was registered in newtons (N). Fracture pattern was assessed and described as favorable or unfavorable. The results were statistically analyzed by 1-way analysis of variance and the post hoc Tukey test with significant statistical difference at P < 0.05. Results: Higher fracture resistance results were found for GC (1,128.35 ± 249.17), GMGIC (1,250.77 ± 173.29), and GN (1,277.22 ± 433.44) (P < .05). More favorable fractures were observed in the GCO (6), GC (7), and GN (7) (P < .05). Conclusion: Teeth restored with composite and modified GIC presented the same resistance as intact teeth. Teeth restored with Coltosol and GGIC presented similar resistance to unrestored teeth.